2007
DOI: 10.1111/j.1468-2982.2007.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Osmophobia in Migraine and Tension-Type Headache and Its Clinical Features in Patients With Migraine

Abstract: Intolerance to smell is often reported by migraine patients. This study evaluates osmophobia in connection with the diagnosis of migraine and episodic tension-type headache (ETTH). The characteristics of this symptom are also investigated. We recruited from our Headache Centre 1005 patients (772 female, 233 male; age 37 +/- 11 years), of whom 677 were migraine without aura (MoA), 130 migraine with aura (MA) and 198 TTH. Patients with two or more forms of primary headache were excluded. Among migraine patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
118
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(149 citation statements)
references
References 33 publications
(34 reference statements)
26
118
1
2
Order By: Relevance
“…The majority of studies investigated the presence of osmophobia. There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies investigated the presence of osmophobia. There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, we observed a severe intolerance to odours, pleasant or unpleasant, during headache attacks. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, a limited number of studies showed that odours may trigger headache attacks in some patients, particularly in migraineurs 1,3,6,7,9,24 and occasionally in cluster headache patients. 12,18 This intolerance to odours is known as osmophobia, and according to two studies that investigated osmophobia in secondary headaches, it occurred during headache attacks only in the primary headaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although osmophobia is not a diagnostic criterion for migraine, many studies show that this symptom is highly prevalent and is useful to differentiate migraine from tension-type headache [1,4,5,7,8,13]. Such as headache, osmophobia affects the quality of life of migraine patients and hinders the performance of their professional activities, especially in those who work in environments with strong odors, such as in perfumery, gas station and the selling of insecticide or beauty products [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant association between odors and primary headaches, particularly to migraine with or without aura [1][2][3][4][5][6] and tension-type headache [1,[6][7][8]. The literature of its occurrence in secondary headaches is very scarce [9].…”
Section: Introductionmentioning
confidence: 99%